2020
DOI: 10.1177/1179554920936605
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hyponatraemia Before Surgery in Patients With Radical Resected Pancreatic Cancer

Abstract: Objectives: Hyponatraemia represents a negative prognostic factor in patients with cancer. The aim of this study was to assess, for the first time, the role of hyponatraemia in patients undergoing radical surgery for pancreatic ductal adenocarcinoma. Methods: A total of 89 patients with stage I-III pancreatic ductal adenocarcinoma underwent radical surgery between November 2012 and October 2014. Relapse-free survival (RFS) and disease-specific survival (DSS) were estimated using Kaplan-Meier method. A Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Twelve studies included patients who underwent orthopedic surgeries ( 16 , 18 , 24 , 27 , 32 , 33 , 35 , 38 , 41-43 , 45 ); 10 studies involved patients who underwent liver transplantation ( 5 , 7 , 26 , 29 , 31 , 36 , 39 , 40 , 46 , 48 ); 4 studies for cardiac surgical procedures ( 17 , 28 , 37 , 44 ); 3 studies on surgeries of multiple disciplines ( 9 , 14 , 30 ); and 1 study each on radical gastrectomy ( 47 ), surgical procedures for epithelial ovarian cancer ( 34 ), and radical surgical procedures for pancreatic ductal adenocarcinoma ( 25 ). Sixteen studies included patients from North America ( 5 , 7 , 14 , 16-18 , 27 , 28 , 30 , 32 , 35 , 37-39 , 42 , 43 ), 8 studies from Europe ( 9 , 25 , 29 , 34 , 36 , 40 , 41 , 45 ), 5 from Asia ( 31 , 33 , 46-48 ), 2 from South America ( 24 , 26 ), and 1 from Israel ( …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies included patients who underwent orthopedic surgeries ( 16 , 18 , 24 , 27 , 32 , 33 , 35 , 38 , 41-43 , 45 ); 10 studies involved patients who underwent liver transplantation ( 5 , 7 , 26 , 29 , 31 , 36 , 39 , 40 , 46 , 48 ); 4 studies for cardiac surgical procedures ( 17 , 28 , 37 , 44 ); 3 studies on surgeries of multiple disciplines ( 9 , 14 , 30 ); and 1 study each on radical gastrectomy ( 47 ), surgical procedures for epithelial ovarian cancer ( 34 ), and radical surgical procedures for pancreatic ductal adenocarcinoma ( 25 ). Sixteen studies included patients from North America ( 5 , 7 , 14 , 16-18 , 27 , 28 , 30 , 32 , 35 , 37-39 , 42 , 43 ), 8 studies from Europe ( 9 , 25 , 29 , 34 , 36 , 40 , 41 , 45 ), 5 from Asia ( 31 , 33 , 46-48 ), 2 from South America ( 24 , 26 ), and 1 from Israel ( …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies defined hyponatremia as serum sodium levels of either < or ≤135 mEq/L ( 5 , 14 , 16-18 , 24 , 25 , 28-30 , 32-35 , 37 , 38 , 41-46 ), 8 defined hyponatremia as either < or ≤130 mEq/L ( 7 , 26 , 31 , 36 , 39 , 40 , 47 , 48 ), 1 study used the cut off of ≤137 mEq/L to define hyponatremia ( 9 ), and 1 study did not specify the numerical definition of hyponatremia ( 27 ). Three of the studies reported outcomes stratified by the degree of severity of hyponatremia of patients ( 9 , 16 , 29 ).…”
Section: Resultsmentioning
confidence: 99%